The Genealogy of Hatred: An Analysis of Traditional Islamic Philosophy in the Contemporary World - Ziaul Haq, Mochamad (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2025)
This study aims to explore the root causes of hatred from the perspective of classical Islamic philosophy by analyzing key concepts such as nafs (soul), ghadhab (anger), ‘aql (intellect), and hikmah (wisdom) in the works of prominent Muslim philosophers: Al-Ghazali, Al-Farabi, and Ibn Miskawayh. The research is motivated by the increasing prevalence of hate speech and polarization in the digital public sphere, which reflects a deeper moral and spiritual crisis. Using a qualitative approach with library research and a historical-hermeneutic method, the study conducts a conceptual analysis of classical texts and links their insights to contemporary social phenomena. The findings indicate that hatred is not merely an emotional outburst but a symptom of moral failure, stemming from the dominance of uncontrolled desires and the marginalization of ethical reasoning. Al-Ghazali emphasizes that unmanaged anger (ghadhab) leads to destructive hatred when not purified through tazkiyatun nafs. Al-Farabi highlights the integrative role of intellect and heart, while Ibn Miskawayh underscores the importance of ethical training (riyāḍatu al-nafs) to prevent moral decay. These philosophical perspectives offer a comprehensive ethical framework for addressing hatred, surpassing the limitations of purely legal or psychological approaches. The implications of this study affirm the need for moral and spiritual education in both formal and informal institutions. It suggests integrating Islamic philosophical ethics into public policy and educational curricula as a preventive measure against hatred in digital and social spaces. The originality of this research lies in its synthesis of classical Islamic philosophical ethics with current global challenges, offering an alternative epistemological foundation for contemporary hate studies.